KiDS-Legacy: consistency of cosmic shear measurements and joint cosmological constraints with external probes - Stölzner, Benjamin; Wright, Angus H.; Asgari, Marika; Heymans, Catherine; Hildebrandt, Hendrik; Hoekstra, Henk; Joachimi, Benjamin; Kuijken, Konrad; Li, Shun-Sheng; Mahony, Constance; Reischke, Robert; Yoon, Mijin; et al. (Astronomy and astrophysics, 2025)
We present a cosmic shear consistency analysis of the final data release from the Kilo-Degree Survey (KiDS-Legacy). By adopting three tiers of consistency metrics, we compared cosmological constraints between subsets of the KiDS-Legacy dataset split by redshift, angular scale, galaxy colour, and spatial region. We also reviewed a range of two-point cosmic shear statistics. As all the data passed our set of consistency metric tests, we demonstrate that KiDS-Legacy is the most internally consistent KiDS catalogue to date. In a joint cosmological analysis of KiDS-Legacy and DES Y3 cosmic shear, combined with data from the Pantheon+ Type Ia supernovae compilation and baryon acoustic oscillations from DESI Y1, we report constraints that are consistent with Planck measurements of the cosmic microwave background, with and .
Online veröffentlicht: 17. Oktober 2025
Gesehen am 05.01.2026